Improving Access to Medicines in Poor Countries: The Role of Universities - Chokshi, Dave A (Public Library of Science, 2006)
Universities Allied for Essential Medicines, a coalition of students and faculty across North America, focuses on how academic research institutions can help to improve access to essential medicines.